Characterizing the relationships between dietary indices, gallstone prevalence and the need for gallbladder surgery in the general US population - Jiang, Chenyu; Shao, Yaojian (Frontiers in Nutrition, 2024)
Background: The dietary inflammatory index (DII) and composite dietary antioxidant index (CDAI) were developed as tools for use when seeking to assess the potential inflammatory and antioxidant activity of a given diet, respectively. The associations between these indices and gallstone incidence remain largely unexplored. Objective: The present study sought to clarify how both the DII and the CDAI are related to gallstone incidence and age at first gallbladder surgery among adults in the USA. Methods: Cross-sectional data from the 2017-2020 cycles of the National Health and Nutrition Examination Survey (NHANES) pertaining to 12,426 individuals were used to conduct the present study. Data from two days with 24 h dietary recall were employed when calculating DII and CDAI scores. Relationships between dietary indices and the incidence of gallstones were assessed through logistic regression analyses, while linear regression analyses were employed to characterize how these indices are associated with the age at first gallbladder surgery. Results: Higher DII scores and lower CDAI scores, which respectively denote diets with greater inflammatory potential and reduced antioxidant potential, were found to be associated with higher gallstone incidence even following adjustment for potential confounding factors. Smooth curve fitting suggested that the association between DII and gallstones was nearly linear, whereas that between CDAI and gallstone incidence was nonlinear. Higher DII values were also related to first gallbladder surgery at an earlier age (β = -0.64, 95% CI: −1.26, −0.02). Conclusion: These results emphasize the benefits of anti-inflammatory diets rich in antioxidants, which may help reduce gallstone incidence among adults in the USA. Higher DII scores may also predict the need for gallbladder surgery at a younger age.